Assessment of eating and lifestyle habits among Polish cosmetology and physiotherapy students - Alicja Szypowska; Małgorzata Jeziorek; Bożena Regulska-Ilow (National Institute of Public Health - National Institute of Hygiene, 2020)
Background. Proper nutritional behaviors are one of the most important factors shaping our health, as they influence people's physical and mental state. Good eating habits help prevent many chronic diseases, including cardiovascular disease, type II diabetes, some types of cancer, and osteoporosis. The Polish population aged 20-34 years displays improper nutritional behaviors which may put them at risk of developing diet-dependent diseases in the future. There is a need to assess students' lifestyle, including their eating habits, as it would help adapt already existing education programs. Objective. We evaluated and compared eating habits and lifestyle of students studying cosmetology and physiotherapy in association with selected risk factors of civilization diseases. Material and methods. We used a standardized dietary questionnaire evaluating respondents' physical activity, smoking and dietary habits. The obtained results were compared with the recommendations from the Polish food-based dietary guidelines. We evaluated respondents' nutritional status based on their anthropometric measurements such as body weight, body height, hips and waist circumferences and then we estimated their body mass index (BMI) and waist hip ratio (WHR). Results. Students studying cosmetology and physiotherapy obtained on average 5.3 ±1.5 points based on their compliance with the nutritional recommendations. The academic youth did not meet principles of healthy nutrition according to the given recommendations. There were no significant differences in nutrition status between the faculties, except for products that provide complete protein. Conclusions. There is a need to increase nutritional awareness of academic youth, especially students of health-related faculties, because better knowledge on nutrition would help them choose healthier food options.